Resolution of labor conflicts: case of negotiation of a collective contract in Codelco (Chile) - Jorge Cea Rodríguez; Jorge Riveros Sudy; Roberto Cárdenas Gutiérrez (Estudios de Administración, 2019)
Codelco is a state owned enterprise, the world’s leading producer of copper in the world, a leader in planetary reserves of ore and the engine of Chile’s development. It is dedicated to exploring mining resources, processing them to produce refined copper and by-products, and then marketing them to customers worldwide. The main market is Asia, followed by Europe and South America. This work is done through eight mining divisions. The case looks at labor conflict resolution between the Codelco mineral company (in the mining division of Chuquicamata) and the worker’s union in a collective bargaining process. The collective bargaining process had different stages, from the first offer given by the “Prompt Firm” company, through the process of “Mediation of Good Offices”, the beginning of the legal strike, the last negotiation until finally achieving the end of the legal strike and the agreement between the parties. The agreement of the unions with the “Improved Final Offer” of the company meant that after agreeing a bonus for the end of conflict of 14.1 million pesos and a salary readjustment of 1.2 percent, the workers had to return to their jobs. The next collective bargaining would be in 3 years. A contextualization and description of the collective bargaining process is carried out based on published journalistic information about the case and some scientific sources. In the end a series of questions are raised to generate a discussion in a Human Resource Management class.